SEDIMENTOLOGY OF THE CHARU FORMATION, SUNGAI LEMBING AREA, PAHANG, PENINSULAR MALAYSIA - ONG, KAR YING (2017)
The Charu Formation of the Kuantan Group is exposed across the Sungai Lembing area in Pahang. This Lower Carboniferous formation of the Kuantan Group is conformably overlain by the Panching Limestone and Sagor Formation. This formation was investigated with detailed logging of outcrops and analysis of sedimentological characteristic in order to understand the depositional facies and sedimentary environment. This study targets the onshore sedimentary successions exposed in Northwest Pahang, from Sungai Kenau to the Sungai Lembing-Kuantan road. The Charu Formation is located at Sungai Lembing town. The research area covers approximately 300 square kilometers from longtitudes 103˚ 01’58” E and 103˚ 02’05” E and latitudes 3˚ 54’ 55”N and 3˚ 55’03” N. This study reveals the presence of nine lithofacies: Large-scale Cross-stratified sandstone Facies, Small-scale cross-stratified sandstone Facies, Climbing ripple cross-stratified sandstone Facies, Wave rippled sandstone Facies, Low angle cross-stratified sandstone Facies, Horizontally bedded sandstone Facies, Amalgamated hummocky cross-stratified (HCS) to swaley cross-stratified (SCS) sandstone Facies, Interbedded sandstone and mudrocks/ Heterolithic bedding Facies and Mudrocks Facies. Based on the nine facies discovered, two facies associations could be deduced from the nine lithofacies; a.) Inner Shelf Lower Shoreface Facies Association, b) Inner Shelf Offshore Transition Facies Association, c) Delta Front Mouth Bar Facies Association and d) Nearshore Facies Association. The facies association in Charu Formation are interpreted as a regressive nearshore succession over the marine inner shelf. Facies architecture analysis could be done on the series of sandstone north-east of Sungai Lembing area towards the boarder of Terengganu. A complete stratigraphic section of Kuantan Group has not yet been completed. This research should proceed in collecting borehole data. The borehole samples would be suitable for micropaleontological analysis and biostratigraphic analysis could be carried out.